A review of the geomorphotectonic evolution of the south Malawi rift. (May 2017) - Dulanya, Zuze
Abstract: Landscape evolution is a complicated process responding to geological, geomorphological and climatic processes which are preserved in the geological record. Sediment archives play an important role in paleo-environmental reconstructions especially in areas where sediment preservation is good. However, in some areas where preservation is poor, use of sediment archives can be a problem. One such area is the Middle Shire area near the southern end of the Malawi Rift within the western branch of the East African Rift System. The area adjoins the NW-trending lower Shire Basin to Lake Malawi-Upper Shire Rift and is key to the understanding of geomorphotectonic processes in the latter part of the Cenozoic despite the absence of well-developed basins and sediment archives. This study is a review of the evolution of the geomorphotectonic history of the area based on integration of existing geomorphotectonic information of the southern-end of the Middle Shire basin. Results suggest that the Middle Shire section is a younger development which connected the Lower Shire to the Upper Shire section and the existence of an earlier drainage system in the lower Upper Shire section (paleo-Rivirivi) during the Plio-Pleistocene times. Highlights: The Middle Shire area consists of a number of knick points joining two erosional surfaces. That the upper and lower shire river sections previously formed two separate rivers. The Upper Shire section is younger than the Lower Shire section.